2016
DOI: 10.1111/are.13178
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultrafiltered fish protein hydrolysate levels on the liver and muscle metabolic profile of juvenile turbot (Scophthalmus maximusL.) by1H NMR-based metabolomics studies

Abstract: A 1H NMR‐based metabolomics approach was to explore the effect of ultrafiltered fish protein hydrolysate (UF) levels on the liver and muscle metabolic profile of juvenile turbot (Scophthalmus maximus L.). Fish protein hydrolysate (FPH) was produced from by‐products by enzymatic treatment, and UF was obtained by diluting FPH followed filtration. Fish were fed diets containing fish meal protein, which was, respectively, replaced by UF protein 0, 50, 100, 150 and 200 g kg−1 of dietary total protein (UF‐0, UF‐5, U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Ultrafiltered fish protein hydrolysate to replace crude FM especially tended to decrease lactate, fumarate and alanine (Wei et al . ). The total substitution of crude Baltic FM and FO, which accumulate persistent organic pollutants, by decontaminated FM and semi‐purified FO highlighted the role of energy‐related metabolites such as pyruvate.…”
Section: Dietary Modulations Of Fish Metabolismmentioning
confidence: 97%
See 3 more Smart Citations
“…Ultrafiltered fish protein hydrolysate to replace crude FM especially tended to decrease lactate, fumarate and alanine (Wei et al . ). The total substitution of crude Baltic FM and FO, which accumulate persistent organic pollutants, by decontaminated FM and semi‐purified FO highlighted the role of energy‐related metabolites such as pyruvate.…”
Section: Dietary Modulations Of Fish Metabolismmentioning
confidence: 97%
“…The second hypothesis is supported by the higher level of branched chain amino acids found in the liver of juvenile turbot fed a plant‐based diet supplemented with ultrafiltrated fish protein hydrolysate (Wei et al . ). The authors suggested that a large supply of these amino acids by hydrolysates stimulates their use for energy supply associated with a reduced gluconeogenesis.…”
Section: Dietary Modulations Of Fish Metabolismmentioning
confidence: 97%
See 2 more Smart Citations
“…A metabolomic approach based on nuclear magnetic resonance (NMR) was used to investigate the effect of feed deprivation in rainbow trout plasma (Kullgren, Samuelsson, Larsson, Björnsson, & Bergman, ) and to analyse the metabolic changes due to diet composition in various fish species (Abro, Moazzami, Lindberg, & Lundh, ; Asakura, Sakata, Yoshida, Date, & Kikuchi, ; Mannina et al., ; Schock, Newton, Brenkert, Leffler, & Bearden, ; Wagner, Trattner, Pickova, Gómez‐Requeni, & Moazzami, ; Wei, Liang, Mai, Zheng, & Xu, ). This approach was implemented to correlate faecal metabolites with intestinal microbiota in fish (Asakura et al., ).…”
Section: Introductionmentioning
confidence: 99%